The application of artificial intelligence assistant to deep learning in teachers' teaching and students' learning processes - Liu, Yi; Chen, Lei; Yao, Zerui (Frontiers in Psychology, 2022)
With the emergence of big data, cloud computing, and other technologies, artificial intelligence (AI) technology has set off a new wave in the field of education. The application of AI technology to deep learning in university teachers' teaching and students' learning processes is an innovative way to promote the quality of teaching and learning. This paper proposed the deep learning-based assessment to measure whether students experienced an improvement in terms of their mastery of knowledge, development of abilities, and emotional experiences. It also used a comparative analysis of pre-tests and post-tests through online questionnaires to test the results. The impact of technology on teachers' teaching and students' learning processes, identified the problems in the teaching and learning processes in the context of the application of AI technology, under tAI technology to improve efficiency in teaching and learning, optimize course design, and engage students in deep learning. The contribution of this research is the teaching and learning processes will be enhanced by emphasizing intelligent and efficient teaching on the teachers’ side and personalized and in-depth learning on the student’ side., The findings are helpful for teachers to better grasp the actual conditions of in-class teaching in real time, carry out intelligent lesson preparations, enrich teaching methods, improve teaching efficiency, and achieve personalized and precision teaching. On the other hand, it also provides a space of intelligent support for students with different traits in terms of learning and effectively improves students' innovation ability, ultimately achieving the purpose of "artificial intelligence + education.”